Capecitabine plus paclitaxel induction treatment in gastric cancer patients with liver metastasis: a prospective, uncontrolled, open-label Phase II clinical study. (September 2016) - Wu, Ai-Wen; Yuan, Peng; Li, Zi-Yu; Tang, Lei; Bu, Zhao-De; Ren, Hui; Ji, Jia-Fu
Aim: To determine the overall survival rate, radical resection rate, objective response rate and safety of capecitabine plus paclitaxel induction chemotherapy in gastric cancer patients with liver metastases.Patients & methods: A total of 30 patients (median age: 59.5 years) diagnosed as gastric adenocarcinoma with liver metastasis received ≥3 cycles of capecitabine and paclitaxel therapy followed by radical resection 4–6 weeks after termination of chemotherapy.Results: The median survival time was 11.4 months, and the objective response rate was 53.3%. The radical resection rate was 23.3% (95% CI: 9.9–42.3). Major toxicities included grade 3 neutropenia (10.0%) and grade 3 diarrhea (3.3%).Conclusion: Capecitabine plus paclitaxel chemotherapy may be effective and safe to improve overall survival and the resection rate of gastric cancer patients with liver metastases.ClinicalTrials.gov identifier: NCT0116704.